Actions undertaken to further small and medium enterprises development in the Silesian Voivodeship, Poland - Olga Okrzesik (Economic and Environmental Studies (E&ES), 2017)
The article focuses on the ongoing activities in the Silesian Voivodeship for the purpose of developing enterprises from the SME sector, inter alia, through increasing innovation. An analysis of desk research strategies and regulations in the Silesian Voivodeship facilitating the growth of a company's position on the market was made in the work, which should also translate into the region's growth. This article consists of a section on the characteristics of the region and presents the implemented activities in a synthetic way (including innovative and regional policy in the Silesian Voivodeship).
Keywords: L10; L22; O10; O31; 330; development strategies; Small and Medium Enterprises; innovation